Efficient degradation of tetracycline over vacancy-modified Cu-doped Bi2O2S via peroxymonosulfate activation and photocatalysis. (10th May 2023) - Xing, Yonglei; Jiang, Xiaojing; Han, Lei; Jin, Xiaoyong; Ni, Gang; Peng, Yage; Yong, Xiaojing; Wang, Xin
Abstract: Herein, Cu-doped Bi2 O2 S catalysts with abundant oxygen vacancies (abbreviated Cu/BOS-OV) were prepared by calcining one-step hydrothermally synthesized Cu-doped Bi2 O2 S in a tube furnace. The photodegradation efficiency of tetracycline (TC, 15 mg L −1 ) over Cu/BOS-OV reached 79% under visible light owing to the introduction of impurity bands by Cu doping and oxygen vacancies, improving the separation efficiency of photogenerated carriers. However, the Cu/BOS-OV catalyst achieved an efficiency of 90.4% for 30 mg L −1 TC degradation within 30 min due to peroxymonosulfate (PMS) activation by oxygen vacancies and copper ions. The intermediates of TC degradation were analyzed by LC‒MS, and the possible decomposition process of TC was proposed. The free radical trapping and ESR experiments showed that ·O2 −, 1 O2, and ⋅OH/SO4 − participated in the degradation of TC. Furthermore, the free energy diagram of HSO5 − dissociation and ·OH/SO4 − desorption processes indicated that the enhanced PMS activation efficiency toward TC degradation was contributed by the decreased adsorption energy and increased O–O bond length of HSO5 − on Cu/BOS-OV. This study provides good application prospects for removing organic contaminants based on photocatalysis and PMS activation technology. Graphical abstract: Image 1 Highlights: Both Cu 2+ doping and oxygen vacancies could activate PMS and produce SO4 . − The oxygen vacancies could introduce abundant active sites. O2 −, 1 O2, and OH/SO4 . − were the main active species in the TC degradation The adsorption energy of HSO5 − on Cu/BOS-OV were reduced. The O–O bond length of HSO5 − on Cu/BOS-OV increased.